Analisa Penerapan Sekuen T1 Spir Dan Sekuen Dwi Pada Pemeriksaan Mri Pelvis Dengan Kontras Pada Klinis Fistula Perianal - Alfian Nur; Made Adhi Mahendrayana; Hendra Setiawan (Catha : Jurnal Penelitian Kreatif dan Inovatif, 2025)
Background: Perianal fistula is an anorectal disorder characterized by the formation of an abnormal channel between the anal canal and the perineum due to infection of the anal glands. Pelvic MRI with contrast is the imaging modality of choice because it can depict the fistula tract in detail, show sphincter involvement, and detect abscesses or secondary tracts that are difficult to find with other methods. Method: The research method used was descriptive qualitative with a case study approach to one patient diagnosed with perianal fistula. The examination procedure included patient preparation, intravenous administration of the contrast medium Dotarem, and an MRI sequence protocol comprising T2W_SPAIR, T2W_TSE, pre- and post-contrast T1W_SPIR, and DWI. The examination was performed using a 1.5 Tesla MRI scanner with a fish oil capsule marker (natural) to mark the location of the external fistula.  Results: The imaging results showed an active fistula tract from the internal opening at 5 o'clock direction of the anus to the skin surface without secondary tracts or additional abscesses. In conclusion, pelvic MRI with contrast provides a detailed anatomical picture of the perianal fistula and assists in planning appropriate medical treatment. Keywords: Pelvic MRI, Perianal Fistula, SPIR, DWI, and marker nature